PENGUJIAN RELIABILITY APLIKASI SMART CITY MENGGUNAKAN TEKNIK PENGUJIAN EKSPLORASI BERBASIS TUR - Putri, Titis Sari; Zahrati, Wenty (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2022)
Smart City is a solution to overcome various problems in urban areas through interactive internet-based applications that provide various services that can be accessed by the public online. By 2020, more than 50% of the population in Indonesia live in urban areas, and this number will continue to increase in the future. To facilitate urban population services, the government has developed smart city services in various cities since the last 5 years. Such development needs to be supported from various fields, including from the technical side of system development. Smart city applications must be reliable so that they can be used properly by the community. In this study, reliability testing was carried out on six smart city applications in six cities, namely Live Tangerang, Sadayana Bandung, Jogja Smart Services, Cimahi SmartCity, Nganjuk Smart City and Tuban Smart City using tour-based exploratory testing techniques. The test results show that there are deficiencies or bugs found in the form of inconvenience to use because there is no error handling on the input form, an unresponsive interface, unavailability of information, and imperfect navigation. In addition, there are some bugs that are quite annoying, namely the sudden closing of the application when the user uses certain features.